2015
DOI: 10.1002/nav.21663
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic pricing in a dual‐market environment

Abstract: This paper is concerned with the determination of pricing strategies for a firm that in each period of a finite horizon receives replenishment quantities of a single product which it sells in two markets, e.g., a long-distance market and an on-site market. The key difference between the two markets is that the long-distance market provides for a one period delay in demand fulfillment.In contrast, on-site orders must be filled immediately as the customer is at the physical on-site location. We model the demands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 72 publications
(107 reference statements)
0
3
0
Order By: Relevance
“…Chen et al. (2015) determine pricing strategies for a manufacturer in a finite time horizon. They consider two markets, where the first market's demand can be fulfilled by delay but the other market demand should be fulfilled permanently.…”
Section: Pricing Paradigms and Related Literaturementioning
confidence: 99%
“…Chen et al. (2015) determine pricing strategies for a manufacturer in a finite time horizon. They consider two markets, where the first market's demand can be fulfilled by delay but the other market demand should be fulfilled permanently.…”
Section: Pricing Paradigms and Related Literaturementioning
confidence: 99%
“…However, considering that a part of revenue is required to be shared with the e-tailer when accepting the online orders, retailer A always satisfies its own in-store demands with priority. A related work can be found in Chen et al (2015b), where the fashion retailer operates two channels: An on-site physical store and a long distance online store. Different from the physical store where the consumer demand should be fulfilled immediately, the orders from the online store could be delayed for a period.…”
Section: Retailermentioning
confidence: 99%
“…The first well-known supplier uncertainty is all-or-nothing such as [2,10]. In more general case, one way to incorporate the supplier uncertainty into the model is to use a random yield rate [27,8,7],…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the existing literature, it has been proved that both optimal order quantity and optimal price are decreasing as inventory increases when the retailer faces all-or-nothing supplier and demand uncertainties [8,10]. It also has been shown that the optimal order quantity and optimal order price may not be monotonic in the inventory level when both supplier yield uncertainty and multiplicative demand noise are involved (see for example [32,8,7]). Being different from the existing literature, the supplier's risk is captured by capacity uncertainty instead of yield uncertainty in our paper.…”
mentioning
confidence: 99%